Ion chromatograph with three‐dimensional printed absorbance detector for indirect ultraviolet absorbance detection of phosphate in effluent and natural waters. Issue 5 (14th January 2022) - Lace, Annija; Byrne, Aideen; Bluett, Simon; Malaquin, Laurent; Raimbault, Vincent; Courson, Remi; Hayat, Zain; Moore, Breda; Murray, Eoin
Abstract: An ion chromatography system employing a low‐cost three‐dimensional printed absorbance detector for indirect ultraviolet detection towards portable phosphate analysis of environmental and industrial waters has been developed. The optical detection cell was fabricated using stereolithography three‐dimensional printing of nanocomposite material. Chromatographic analysis and detection of phosphate were carried out using a CS5A 4 × 250 mm analytical column with indirect ultraviolet detection using a 255 nm light‐emitting diode. Isocratic elution using a 0.6 mM potassium phthalate eluent combined with 1.44 mM sodium bicarbonate was employed at a flow rate of 0.75 mL/min. A linear calibration range of 0.5 to 30 mg/L PO4 3− applicable to environmental and wastewater analysis was achieved. For retention time and peak area repeatability, relative standard deviation values were 0.68 and 4.09%, respectively. Environmental and wastewater samples were analyzed with the optimized ion chromatography platform and the results were compared to values obtained by an accredited ion chromatograph. For the analysis of environmental samples, relative errors of <14 % were achieved. Recovery analysis was also carried out on both freshwater and wastewater samples and recovery results were within the acceptable range for water analysis using standard ion chromatography methods.